Od ikone do fotografije - Vrdlovec, Zdenko (Monitor ISH, 2006)
The Byzantine cult of the holy images, icons, was based on the dogma of the Incarnation, according to which the Son of God, Jesus, was a visible image of the invisible God the Father. Equally influential, however, were the legends about images acheiropoietoi (not made by human hand), most notably the vera icona and the Turin Shroud. The latter was photographed in 1898, its authenticity confirmed by scientific analyses of the negatives. Thus the photograph itself became a new kind of "true image", vera icona, although one rejected by the Church.
Keywords: fotografija; photography; umetnost; art; Bizanc; ikone; ikonoklazem; inkarnacija